The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1111/j.1747-7379.2002.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

The Living Arrangements of Children in Immigrant Families in the United States

Abstract: Little is known about the living arrangements of first‐ and second‐generation immigrant children. Using data from the Current Population Survey and a multivariate approach, I compared living arrangements of immigrant children to U.S.‐born white children with U.S.‐born parents. Findings show, except for foreign‐born black and some Hispanic children, that foreign‐born children lived with married parents more frequently than did U.S.‐born white children with U.S.‐born parents. However, by the third generation, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 6 publications
1
31
0
2
Order By: Relevance
“…Both studies also show diversity in living arrangements by country of origin and ethnicity. In the US study, children of Asian origin were the least likely to be living in single-parent families when compared with Mexican, other Hispanic, Black and White children (Brandon 2002). In the Canadian study, women from Southern European, Asian, Caribbean and Latin American countries were more likely to be living with kin than those from Western or Eastern European countries (Boyd 1991).…”
Section: Previous Studies Of Immigrant Households and Living Arrangemmentioning
confidence: 96%
See 1 more Smart Citation
“…Both studies also show diversity in living arrangements by country of origin and ethnicity. In the US study, children of Asian origin were the least likely to be living in single-parent families when compared with Mexican, other Hispanic, Black and White children (Brandon 2002). In the Canadian study, women from Southern European, Asian, Caribbean and Latin American countries were more likely to be living with kin than those from Western or Eastern European countries (Boyd 1991).…”
Section: Previous Studies Of Immigrant Households and Living Arrangemmentioning
confidence: 96%
“…A study of immigrant children in the United States has found that they are more likely to live with married parents than with single parents compared with native-born children of native-born parents (Brandon 2002), while a study of the living arrangements of elderly foreign-born women in Canada shows that those who migrate at age 65 or later to reunite with family members are much more likely to live with family and less likely to live alone than those who migrated when they were young adults (Boyd 1991). Both studies also show diversity in living arrangements by country of origin and ethnicity.…”
Section: Previous Studies Of Immigrant Households and Living Arrangemmentioning
confidence: 98%
“…Autores como Peter David Brandon (2000) han sostenido, a través de la explotación de los datos del Current Population Survey, que los niños hispanos nacidos en el extranjero viven en mayor medida en hogares con ambos padres de lo que lo hacen los niños blancos nacidos en los EE.UU. Es decir, según su tesis, a medida que la población extranjera se asienta en la sociedad de recepción, aumenta la incidencia de la monoparentalidad entre estos colectivos, acomodándose las pautas familiares a las americanas.…”
Section: La Incidencia De La Monoparentalidad Entre Las Mujeres Inmigunclassified
“…Brandon (2002) suggests that the social capital (e.g., social support) of some immigrant families erodes with the rate of changed residence and second-generation status. Crosnoe (2007) found that children from Mexican immigrant families tend to enter lower-status segments of U.S. society, where powerful socioeconomic disadvantages are combined with equally potent forces such as segregation and discrimination.…”
Section: Children Born In Mexico or Other Parts Of Latin America Andmentioning
confidence: 99%